Pertanggungjawaban Pemerintah Desa terhadap Anggaran Dana Desa yang Tidak Terserap dalam Pembangunan - Bahri, Syaiful; Muhibbin, Mohammad; Suratman, Suratman (JURNAL USM LAW REVIEW, 2024)
This research aims to find out the form of responsibility of the government of Tlontoraja Village, Pasean District, and Pampekasan District for the village funds that are not absorbed by the village development program. The maintenance of government authority through the authority of the government at the village level is charged by APBDes. The flow of village funds in Tlontoraja village obtains funding that comes from the village's original income. Details of the financial value of the village are channeled, among other things, in the amount of 40% for direct cash aid from the country's funds, 20% for food resilience, 1.5% for disaster management, and the rest for material development. The application procedure for the liquidation of village funds is divided into four stages, i.e., 30% for each stage, starting from stages I–IV. At each stage of such liquidation, the mechanism requires the form of accountability of the relevant village government. The method used in this research is based on a sociological, juris-empirical approach. The data collection technique is done using the interview technique. The results of the analysis show that if there is a budget that does not absorb the development of the village, then it should be channeled to the Silpa Fund. The research also does not show any misuse of the village budget funds by the Tlontoraja Village Government.Penelitian ini bertujuan untuk mengetahui bentuk pertanggungjawaban Pemerintah Desa Tlontoraja, Kec. Pasean, Kab. Pamekasan terhadap dana desa yang tidak terserap oleh program pembangunan desa. Penyelenggaraan wewenang pemerintahan melalui kewenangan pemerintah setingkat desa mendapat biaya dari APBDes. Aliran anggaran dana desa di Desa Tlontoraja memperoleh pendanaan yang bersumber dari pendapatan asli desaPerincian nilai keuangan desa yang disalurkan, antara lain, sebesar 40% untuk bantuan langsung tunai dana desa, 20% untuk ketahanan pangan, 1,5% untuk penanggulangan bencana, dan selebihnya untuk pembangunan bersifat material. Prosedur permohonan untuk pencairan dana desa dibagi dalam empat tahap, yaitu sebesar 30% untuk masing-masing tahap mulai dari tahap I – IV. Pada tiap-tiap tahapan pencairan tersebut, mekanisme mewajibkan bentuk pertanggungjawaban dari pemerintah desa terkait. Metode yang digunakan dalam penelitian ini adalah yuridis-empiris berbasis pendekatan yuridis sosiologis. Teknik pengumpulan data dilakukan dengan teknik wawancara. Hasil pengkajian menunjukkan bahwa jika terdapat anggaran yang tidak terserap pembangunan desa maka harus disalurkan ke dana Silpa. Hasl penelitian juga tidak menunjukkan adanya penyalahgunaan anggaran dana desa disalahgunakan oleh Pemerintah Desa Tlontoraja.